Language-Independent and Language-Specific Aspects of Early Literacy: An Evaluation of the Common Underlying Proficiency Model - Goodrich, J. Marc (J Educ Psychol, 2017)
According to the common underlying proficiency model (Cummins, 1981), as children acquire academic knowledge and skills in their first language, they also acquire language-independent information about those skills that can be applied when learning a second language. The purpose of this study was to evaluate the relevance of the common underlying proficiency model for the early literacy skills of Spanish-speaking language-minority children using confirmatory factor analysis. Eight hundred fifty-eight Spanish-speaking language-minority preschoolers (mean age = 60.83 months, 50.2% female) participated in this study. Results indicated that bifactor models that consisted of language-independent as well as language-specific early literacy factors provided the best fits to the data for children’s phonological awareness and print knowledge skills. Correlated factors models that only included skills specific to Spanish and English provided the best fits to the data for children’s oral language skills. Children’s language-independent early literacy skills were significantly related across constructs and to language-specific aspects of early literacy. Language-specific aspects of early literacy skills were significantly related within but not across languages. These findings suggest that language-minority preschoolers have a common underlying proficiency for code-related skills but not language-related skills that may allow them to transfer knowledge across languages.